Public knowledge and perception of COVID-19 and its preventive measures - Sim, Edmund Ui Hang; Ting, Su Hie (Routledge, 2022)
Knowledge from research on the transmission route of SARS-CoV-2 is the backbone for recommendation by WHO on the lockdown and standard operating procedures (SOPs) for prevention. At the start of the pandemic, the transmission mode of SARS-Cov-2 was suggested to be from droplet that is discharged from a distance of up to 1.8 metres (6 ft) when an infected person following coughs and/or sneezes (CDC, 2020b; La Rosa et al., 2020). Possible transmission routes include speaking (Anfinrud et al., 2020; Stadnytskyi et al., 2020), airborne aerosols (Lewis, 2020), contaminated surfaces (van Doremalen et al., 2020), and stool (Holshue et al., 2020). Nevertheless, all coronaviruses can be destabilised by soap (Gibbens, 2020). The three most important SOPs are physical distancing, wearing of face masks when in public, and avoiding crowded and confined spaces. Azlan et al. (2020) found that Malaysians had low adherence to preventive measures and feared testing (Yau et al., 2020) although they professed good knowledge of COVID-19. The factors that influence perceived effectiveness of COVID-19 preventive measures and adoption of these measures are still not well understood. This chapter reports the results of a study on health literacy among Malaysians on COVID-19 pandemic, in particular perceived knowledge of COVID-19 disease and effectiveness of preventive measures.